المقاربة الجزائرية لتسوية الأزمة الليبية في ظل التحديات الراهنة - بوستي, توفيق (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
تهدف هذه الدراسة إلى تسليط الضوء على محاور ومضامين المقاربة الجزائرية لحل الأزمة الليبية الراهنة، المنسجمة أساسا مع مبادئ سياستها الخارجية، عبر التركيز على مبدأ الحوار والتأكيد على الحلول السلمية، ورفض كل أشكال التدخل الأجنبي، لقد تم هندسة بحثنا بالاعتماد على المنهج الوصفي والتاريخي و النظمي، ما مكننا من الوصول إلى نتائج ترتبط بمرتكزات المقاربة الجزائرية لحل الأزمة الليبية الراهنة، والقائمة أساسا على ترك السلاح والجلوس إلى مائدة الحوار، لإيجاد حل توافقي يضمن تسوية الأزمة الليبية الراهنة، بما يضمن إستقرار الدولة الليبية، على الرغم من وجود عدة تحديات داخلية وخارجية . Abstract: This study aims to shed light on the contents of the Algerian approach to resolving the current Libyan crisis, which is basically consistent with the principles of its foreign policy, by focusing on the principle of dialogue and emphasizing peaceful solutions, and rejecting all forms of foreign intervention, Our research has been engineered by relying on the descriptive ,historical and systemic approach, which enabled us to reach results related to the foundations of the Algerian approach to resolving the current Libyan crisis, which is based mainly on abandoning arms and sitting at the dialogue table , to find a consensual solution that guarantees the settlement of the current Libyan crisis, in a manner that guarantees the stability of the Libyan state ,although there are seval internal and external challenges.